The impact of continuous professional development activities on student learning outcomes and employability - Nassereddine, Mohamad; Nassreddine, Ghalia (International Journal of Evaluation and Research in Education (IJERE), 2024)
The fast development of engineering technologies forces a wide range of students to choose the technological path for their careers. Universities focus on theoretical study with limited practical exposure. To ensure students are prepared for the industry requirements, engineering universities set a core industrial experience for all students. This industrial experience aims to bridge the gap between academia and industry and to ensure students have gained the required industrial. The work in this paper highlights the importance of continuous professional development (CPD) hours for engineering students. The paper studies the impact of CPD hours on the critical skills of the student learning outcomes. A descriptive analytical methodology is applied to examine this impact. Thus, a survey of 34 questions was created and distributed to students at engineering schools in different universities across the MENA and Gulf Region. A sample of 234 answers is collected and analyzed using a statistical package for the social sciences (SPSS). The results show that students agree that CPD activities can enhance their learning outcomes, teamwork skills, public speaking, and technical competencies. The results show that student believes that CPD activity may enhance their chance of securing employment within a short timeline after graduation.